2014
DOI: 10.1016/j.jas.2012.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Natural woodland composition and vegetation dynamic during the Linearbandkeramik in north-western Europe (central Belgium, 5200–5000 b.c.)

Abstract: Natural woodland composition and vegetation dynamic during the Linearbandkeramik in northwestern Europe (central Belgium, 5200-5000 b.c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 14 publications
1
4
0
1
Order By: Relevance
“…At Étaples, up to 13 species were identified, of which 10 taxa did not come from the army's official stock. This number of taxa is consistent with the taxonomic diversity obtained on pre- and protohistorical sites from the north of France and Belgium (Pernaud 1997; Salavert et al 2014). At Étaples, the majority of the archaeological samples may simply represent wood resources available from around the site, rather than a determined selection based on particular species.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At Étaples, up to 13 species were identified, of which 10 taxa did not come from the army's official stock. This number of taxa is consistent with the taxonomic diversity obtained on pre- and protohistorical sites from the north of France and Belgium (Pernaud 1997; Salavert et al 2014). At Étaples, the majority of the archaeological samples may simply represent wood resources available from around the site, rather than a determined selection based on particular species.…”
Section: Discussionsupporting
confidence: 89%
“…A minimum of 50 fragments were identified in each archaeological sample, and for each new taxon determined, an additional 50 fragments were again identified. For temperate Europe, this was sufficient to predict the “optimal sample size to select and study” so as to have the most complete overview of species diversity exploited for firewood in the past (Chabal 1994, 1997: 33; Salavert et al 2014).…”
Section: Charcoal Analysismentioning
confidence: 99%
“…W okresie wczesnego neolitu obszary Europy Środkowej i Północnej zdominowane były przez lasy liściaste ( Kreuz 2007;Mäckel et al 2009;Bogucki et al 2012;Salavert et al 2014;Sudhaus, Friedmann 2015). W tym zadrzewionym krajobrazie istniały na-.…”
Section: Wprowadzenieunclassified
“…Deciduous forests dominated Central and Northern European environments during the Early Neolithic ( Kreuz 2007;Mäckel et al 2009;Bogucki et al 2012;Salavert et al 2014;Sudhaus, Friedmann 2015). Within this wooded landscape, natural openings in the canopy, caused by lightning strikes, river courses (Kreuz 2007) and in some cases wild ruminant activities (Vera 2000) and would have provided natural pastures or areas for agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Since only one occupation phase was identified at the Żerków archaeological site, it is not possible to relate the presence of Maloideae to human occupation of the area. In recent studies of charcoal found at LBK settlements in Belgium, however, an increase of heliophilous post-pioneer taxa such as Maloideae was observed in the second occupation phase; this means that agro-pastoral activity significantly influenced the development of more open forest communities (Salavert et al 2014). The presence of Maloideae has also been linked to human impacts in the Early and Middle Neolithic of Germany (Kreuz 1992, 2010, Jansen & Nelle 2014.…”
Section: Oak and Hazelmentioning
confidence: 99%